BEYOND THE SORE THROAT: UNVEILING THE THYROID’S HIDDEN TURMOIL - Rosleli, Husna; Hafla, Siti Nabihah Mohamed; Ng, Jo-An; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Subacute thyroiditis (SAT) is an inflammatory thyroid disorder often presenting with anterior neck pain and transient thyroid dysfunction. This case highlights the diagnostic challenges and evolving thyroid function tests (TFT) in a patient initially referred for prolonged throat pain. CASE A 50-year-old female presented with anterior neck pain persisting for two weeks, initially treated with antibiotics for suspected infection. She had no dysphagia, odynophagia, or overt hyperthyroid symptoms but reported a significant weight loss of 6 kg over a year, early satiety, and loss of appetite. Examination revealed tenderness over the thyroid gland with no palpable goiter or lymphadenopathy. Initial TFT showed suppressed TSH <0.01 mIU/L with elevated free T4 of 56.4 pmol/L. Inflammatory markers were raised, with an ESR of 77 mm/hr and CRP of 71.5 mg/L, supporting an inflammatory process. Tumor markers, including CEA, AFP, CA-125, CA 15-3, and CA 19-9, were not elevated, reducing the suspicion for the presence of malignancy. Follow-up TFT showed a rapid transition from hyperthyroidism (TSH <0.01, T4 56.4) to euthyroidism (TSH 1.39, T4 8.6), and subsequently, hypothyroidism (TSH 9.9, T4 7.1). The dynamic TFT pattern, absence of thyroid autoantibodies, and recent upper respiratory symptoms supported the diagnosis of subacute thyroiditis. The patient was started on L-thyroxine 50 mcg OD due to hypothyroid progression, with plans for TFT reassessment in 4 weeks. Referral to gastroenterology for early satiety was deferred, considering the likelihood of thyroid-related symptoms. CONCLUSION This case underscores the importance of recognizing evolving TFT trends in subacute thyroiditis in order to avoid unnecessary interventions. A systematic approach to thyroid dysfunction in medical care is crucial for timely diagnosis and management, bridging the gap between knowledge and clinical practice.